MATERNAL EXPOSURE TO XENOESTROGEN BISPHENOL A ON EMBRYO FETAL DEVELOPMENT AND TERATOGENIC POTENTIAL IN RATTUS NORVEGICUS - K. ROY GEORGE; N. A. MALINI (The Bioscan, 2012)
The potential teratogenic effects and fetal toxicity of environmental estrogenic endocrine disruptors have become a great concern in recent years, and they have yet to be fully characterized. Humans are routinely exposed to bisphenol A (BPA), an estrogenic compound that leaches from dental materials and plastic bottles and beverage containers. The present study was conducted to evaluate embryo toxic and teratogenic effects of BPA exposure during the period of pregnancy in Rattus norvegicus. Pregnant rats were administered 600mg/kg of BPA orally using olive oil as a vehicle from days 0 - 15 of gestation. The control group received olive oil only. On completion of the treatment period, the half of the experimental animals were sacrificed under light anesthesia using ether and the other half was allowed to complete their term and deliver their pups. The body weight, the gravid uterine weight, organ weight, number of implantations, number of corpus lutea, litter size, litter weight and growth rate of the viable offsprings were altered after BPA administration. BPA also induced some abnormal changes in gestation such as resorption of fetuses and teratogenicity. The present study suggested that BPA adversely affected the embryo fetal development of the pregnant female rats.